Prevalencia de infección de herida quirúrgica en pacientes con profilaxis antimicrobiana en cesárea programada - Martínez Padrón, Hadassa Yuef; Polendo-Posadas, Luis Eduardo; Ramos-Hernández, Julia Demetria; Vargas González, Domingo; Paredes Sánchez, Francisco Alejandro; Rivera Vázquez, Patricia (Horizonte Sanitario, 2022)
Objective: To determine the prevalence of surgical wound infections in scheduled HRAEV cesarean sections. Materials and method: Retrospective, descriptive, observational cross-sectional study to determine the prevalence of IHC in patients undergoing scheduled cesarean section with antibiotic prophylaxis in HRAEV. Results: 185 records of patients undergoing scheduled cesarean section were evaluated, aged between 28 to 37 years (48.1%) with an average weight of 81 kg (SD = 10.1) with an average body mass index (BMI) of 30 (SD = 4.24) that is, a BMI between 25.76 and 34.24. Of these, 4 patients (2.16%) presented surgical wound infection during scheduled cesarean section, who received ceftriaxone as PA greater than 120 minutes prior to skin incision, these patients are classified as ASA II and had a BMI greater than 30 kg/m2 and without recorded comorbidities. The most frequent antibiotic prophylaxis time in patients undergoing scheduled cesarean section was >120 minutes (34.08%) and ceftriaxone was administered in 84.86% of the population, which is mostly ASA II (97.83%). 100% of the wounds were superficial. Conclusions: In the present study, it was found that the prevalence of IHC in cesarean sections scheduled in HRAEV was 2.16%, a figure that is below the worldwide prevalence, given that the selected patients did not have some of the risk factors. added risk that increased the risk of SSI compared to other studies. Keywords: Surgical wound, Infection, Antibiotic prophylaxis, Cesarean section